A dual-amplified electrochemiluminescence immunosensor constructed on dual-roles of rutile TiO2 mesocrystals for ultrasensitive zearalenone detection. (10th January 2018) - Zheng, Hongli; Yi, Huan; Lin, Wen; Dai, Hong; Hong, Zhensheng; Lin, Yanyu; Li, Xiuhua
Abstract: Herein, a new sandwich-type electrochemiluminescence (ECL) immunosensor was established on the dual-roles of tetragonal rutile TiO2 mesocrystals (TRM) to realize the sensitive detection of zearalenone (ZEA). On the one hand, the poly (amidoamine) dendrimers (PAAD)-functionalized TRM, combining the advantages of hyper-branched of PAAD and the high nanoporosity, large surface area of TRM, was served as the sensing matrix to immobilize enough capturing antibody, realizing the signal amplification. On the other hand, TRM was applied as an effective probe platform to absorb Ru (bpy)3 2+ and simultaneously immobilize the secondary antibody (Ab2 ). Here, based on the superior properties of TRM and the new bridge of 4-Mercaptophenylboronic acid (4-MPBA) for the high affinity of Ab2 and TRM, a strong and stable ECL emission was realized. Additionally, cysteamine first emerging as a blocker was proved to sensitize the ECL response of Ru (bpy)3 2+, which further amplified the ECL signal, avoiding addition of exogenous coreactants into testing solution. Finally, the sandwich-type ECL immunosensor enabled the real samples detection of ZEA with a lower detection limit and wider linear range.